Map of Middle School Teachers’ Ability to Respond to Changes in Community Culture, Local Wisdom and Literacy in Science Learning in the Digital Era - Wahidin Wahidin; Agus Sumantri (STKIP Singkawang, 2023)
Disruption of information technology has caused changes in community culture and local wisdom in the school life environment. Schools as institutions that prepare graduates with environmentally friendly Pancasila values cannot be separated from community life as a source of learning. The purpose of this study was to map the ability of middle school science teachers to respond to socio-cultural changes in society, the potential of local wisdom, and the demand for student literacy enhancement in learning according to the philosophy of 21st Century Education. The research method used ex-post facto with a descriptive approach. Sample of this study was 15 students of Biology Education Study Program who are compiling theses and undergraduate and master’s degree programs with the theme of linking science learning in schools with 21st century education, cultural change, local wisdom and literacy. To complete the data, a survey was conducted of 500 middle school teachers in West Java through a google form with 33 statements and interview guide. The instruments used questionnaires and interview guide. The results of this study indicated that most teachers have not fully carried out learning according to the philosophy of 21st Century Education. Most teachers were able to carry out the online learning process, design learning through searching content on the internet, videos, YouTube, e-books, and use various applications related to learning according to their expertise. 21st Century Education-oriented learning has not been carried out massively among teachers. There was an increase in student literacy, thinking skills, engineering skills and scientific attitudes. Existing community culture and local wisdom in the school environment were rarely used as a source of learning for the basic values of religion and spirituality, nationalism, and values of human character. The teachers’ ability to respond to changes and increase literacy in building a digital culture remained low due to limited skills in dealing with environmental changes that were difficult for schools to follow.